2020
DOI: 10.1186/s13244-020-00865-8
|View full text |Cite
|
Sign up to set email alerts
|

Blended learning of radiology improves medical students’ performance, satisfaction, and engagement

Abstract: Purpose: To evaluate the impact of blended learning using a combination of educational resources (flipped classroom and short videos) on medical students' (MSs) for radiology learning. Material and methods: A cohort of 353 MSs from 2015 to 2018 was prospectively evaluated. MSs were assigned to four groups (high, high-intermediate, low-intermediate, and low achievers) based on their results to a 20-MCQs performance evaluation referred to as the pretest. MSs had then free access to a self-paced course totalizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 56 publications
2
35
0
1
Order By: Relevance
“…Most of the research articles revealed many advantages of SDL. Self-assessment, identifying skills, and confidence-building were the major advantages cited (1,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Various methods, such as problem-based learning, flipped classroom, and case-based learning, helped students work on themselves to gain knowledge, and analyze and interpret it with critical thinking, and also apply it leading to a definite diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research articles revealed many advantages of SDL. Self-assessment, identifying skills, and confidence-building were the major advantages cited (1,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Various methods, such as problem-based learning, flipped classroom, and case-based learning, helped students work on themselves to gain knowledge, and analyze and interpret it with critical thinking, and also apply it leading to a definite diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A study about Video-Based Learning showed that the effectiveness of this tool is augmented by the teachers' consideration to manage and maximize students' engagement (30). This suggests that when dealing with large cohorts that teach students from many courses, the development of more speci c e-learning materials is required for engagement levels to be maintained.…”
Section: Knowledge Attainmentmentioning
confidence: 99%
“…Young adults make an extensive use of video in their daily lives (49). The use of level-adapted video-based learning (VBL) is a new and innovative concept that meets the expectations of both teachers and students besides VBL increased the motivation of the students (30,50). Real time interactive tutorials such as streaming have been found to be more bene cial than links to a pre-recorded video of the tutorial (22,23).…”
Section: Platformsmentioning
confidence: 99%
“…Using pre-recorded video lectures in e-learning has been previously evaluated for teaching radiological contents to medical students [ 8 , 21 , 23 , 27 , 31 ]. However, to the best of our knowledge, there are no sufficient published data on the use of recorded live virtual sessions.…”
Section: Discussionmentioning
confidence: 99%